Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/ijc.22737
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer survival in the Nordic countries and the United Kingdom: Excess mortality risk analysis of 5 year relative period survival in the period 1999 to 2000

Abstract: A deficit in colorectal cancer survival in Denmark and in the UK compared to Sweden, Norway and Finland was found in the EUROCARE studies. We set out to explore if these differences still exist. Patients diagnosed with colorectal cancer as their first invasive cancer at age 15-89 in the period 1994-2000 were identified using data from 11 cancer registries in the UK and from four Nordic countries. Five-year relative period survival using deaths in 1999-2000 following cancers diagnosed in 1994-2000 was analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 16 publications
5
34
0
1
Order By: Relevance
“…15,16 According to standard practice in population-based cancer survival analysis, relative rather than absolute survival was calculated. Relative survival reflects survival of cancer patients compared to survival of the general population.…”
Section: Design and Methodsmentioning
confidence: 99%
“…15,16 According to standard practice in population-based cancer survival analysis, relative rather than absolute survival was calculated. Relative survival reflects survival of cancer patients compared to survival of the general population.…”
Section: Design and Methodsmentioning
confidence: 99%
“…International variation in survival is greatest in this period,3 suggesting that differences in the quality of care may explain some of the variation. A growing body of evidence also indicates variation in the type and quality of treatment delivered at a national level 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…If variations in the extent of disease at diagnosis or initial treatment account for the observed variations in survival, however, then differences at earlier time points in the course of the disease may be more revealing. For example, recent studies have demonstrated that the greatest differences in survival between the Nordic countries and the UK occurred in the first 6 months after diagnosis 7 8. These differences were also strongly age dependent, with excess mortality and the differences between countries increasing substantially with age.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have presented differences between countries as either cumulative relative survival (usually at 5 years) or relative risk (RR) of increased mortality 7. This can be misleading when the underlying risk is low as even a moderately large RR may have little impact on the number of deaths.…”
Section: Introductionmentioning
confidence: 99%